IMPLEMENTASI KEBIJAKAN TEMPAT PARKIR KHUSUS PADA PARK AND RIDE KERTAJAYA KOTA SURABAYA - Dimas Adhi Pramana; Susi Hardjati (Journal Publicuho, 2023)
This type of research uses a qualitative descriptive research type, with data collection techniques of interviews, observation, and documentation. The results of the study explained that the implementation of the Kertajaya Park and Ride had not been carried out properly as seen from the fact that it was not in accordance with the guidelines in force, but when viewed from the delivery of information it was felt to be good enough, but several approaches were needed. In addition, if seen from community participation, it has been said to be quite good, but several more approaches need to be made. this is proven by the fact that there are still many people who do not understand the purpose of organizing the Kertajaya "Park and Ride" and also abuse the Kertajaya Park and Ride facilities. Meanwhile, the distribution of potential on the responsibility and authority of the executor is considered to be quite effective because the division of management is already in the authority and responsibility of each.